USING CONJUNCTION COORDINATIVE CAPABILITY CLASS X STUDENT OF FARMASI IKASARI SCHOOL PEKANBARU CITY - Amelia, Siska Amelia; Sinaga, Mangatur Sinaga; Burhanudin, Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: At first glance it seems conjunctions do not cause problem. However, in reality, conjunctions play an important role in determiningthe meaning, both in communication (oral) and written. Once the importance of conjunction, the conjunctions into the discussion of the Indonesian language lessons should be taught to students. According to the writer’s observation, learnig conjunctions learned in class X. In this study the authors only studied the coordinative conjunctions. Coordinative conjunctions consists of (1) with the meaning of the sum, (2) the relantionship of meaning perurutan, (3) ties the meaning of the election, (4) the relationship of meaning of resistance, (5) the relationship is more meaning. The formulation of the problem to be investigated in this study is: How does the ability to use the sum of the meaning of conjunctions coordinative relations, perurutan meaning, the meaning of the election, meaning the resistance, and the meaning is more X class high school students of Farmasi Ikasari Pekanbaru city. The purpose of this study were: to use conjunctions coordinative ability knowing the meaning of the summation relationship, perurutan meaning, the meaning of the election, meaning the resistance, and the meaning more high school students in grade X Pekanbaru city of Farmasi Ikasari shool year 2014/2015. The population in this study were high school class X Pekanbaru city of Farmasi Ikasari school year 2014-2015 which amounted to 199 students.while the sample taken was 132 students. This study used a descriptive method aims to describe the ability of the students in understanding coordinative conjunctios, by knowing the form of an instrument of research data about the 50 for objective and 50 for essay. Based the formulation of this problem can be concluded that the ability to use coordinative conjunctions meaning the sum  is classified with average 72,29. Coordinative conjunctions perurutan is classified with average 78,50. Coordinatice conjunctions meaning the selection is high with average 96,40. Coordinative conjunction with the meaning of resistance was callsified as average 73,08. And coordinative conjunctions is high as meaning more to the average 91,10. Keys words: conjunction, conjunctions coordinative, Farmasi Ikasari high school Pekanbaru city